Prevalence of congenital anomalies in babies and associated maternal etiological factors at tertiary care hospital - Chandniwala, Shahana I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was to know the local prevalence of congenital anomaly and study the maternal risk factors associated with it. Methods: Cross sectional descriptive study was carved out. All live babies were examined for presence of congenital anomalies and mother were looked for presence of socio-demographic factor. Results: In this study of 1 year 5767 live birth took place at tertiary care centre out of which 63 babies had congenital anomalies. Therefore, prevalence of congenital anomalies at tertiary care centre was 1.08%. Conclusions: The incidence of malformations were significantly higher in babies born to mothers over the age of 35 years and with parity 4 and above.